Repeatability in column preparation of a reversed-phase C18 monolith and its application to separation of tocopherol homologues - Sirichai Kositarat (2018)
This work investigated the repeatability of column preparation for a reversed-phase C18 monolith, namely stearyl methacrylate-co-ethylene glycol dimethacrylate (SMA-EDMA). The columns were thermally polymerised using three commonly available heating devices (GC oven, hot air oven and water bath) and their chromatographic performance evaluated using micro-liquid chromatography for separation of five test compounds. Precision in terms of %RSD of retention times were 9.0, 6.5, and 12.5 using GC oven, hot air oven and water bath, respectively. Between-batch precision for the hot air oven (n = 3 days) was less than 10.4% for retention time. The SMA-EDMA monolith was applied to the separation of tocopherol homologues by capillary electrochromatography. Usually tocopherol homologues cannot be completely separated by conventional reversed-phase C8- or C18-packed bed or C18-silica based monolithic columns. Polymer monolith has been shown to give remarkable selectivity towards the tocopherols compared to the conventional microparticulate phase and silica based monolith. Successful separation of the tocopherol isomers was achieved on the SMA-EDMA monolith without any column modification. © 2011 Elsevier B.V. All rights reserved.